Implementing a human rights approach to food security - McClain-Nhlapo, Charlotte (International Food Policy Research Institute, 2004)
The premise of a rights-based approach to ensuring adequate food is empowering poor people and those who are food insecure. Empowerment is integral to any strategy that moves away from the benevolence model of food aid and instead emphasizes enabling environments that support people in feeding themselves. Empowerment also removes the full burden of providing food from states. Nevertheless... in the event that people are unable to feed themselves (because of household shocks or other circumstances), the state must accept the responsibility to assist, whether through social safety nets or other programs and policies that protect vulnerable people from hunger. -- from Text